Anodic dissolution of stainless steel in acid solutions - Shtefan, V. V.; Kanunnikova, Nadiia; Leshchenko, S. A.; Balamut, Nataliia (Таврійський національний університет ім. В. І. Вернадського, 2019)
In this work, the kinetics of anodic dissolution of stainless steel was studied using linear voltammetry. It is shown that an increase in the concentration of molybdates leads to an increase in anodic currents and an expansion in the region of active dissolution, which indicates that the oxoanions of the steel surface are passivated. The influence of electrolyte composition on the formation of a passive film was investigated. It has been established that at high potential sweep rates, dense layers of stoichiometric oxide do not have time to form and the passive film has a defective structure. Molybdenum-, zirconium-, aluminum-, titanium-containing compounds have been shown to increase the passivity area, which is the basis for the formation of protective oxide films on stainless steel.

У даній роботі вивчалася кінетика анодного розчинення нержавіючої сталі методом лінійної вольтамперометрії. Показано, що збільшення концентрації молібдатів призводить до збільшення анодних струмів і розширення області активного розчинення, що вказує на пасивацію оксоаніонів поверхні сталі. Досліджено вплив складу електролітів на процес формування пасивної плівки. Встановлено, що при високих швидкостях розгортки потенціалу не встигають утворюватися щільні шари стехиометрічного оксиду, і пасивна плівка має дефектну структуру. Доведено, що молібден, цирконій-, алюміній-, тітанвмісні сполуки збільшують область пасивності, що є підставою для формування захисних оксидних плівок на нержавіючій сталі.
Анодне розчинення нержавіючої сталі в кислих розчинах
Keywords: stainless steel; polarization curves; voltammetry; scan rate; passive film; нержавіюча сталь; поляризаційні криві; вольтамперометрія; швидкість розгортки потенціалу; пасивна плівка